Intestinal microbiota modulation in juvenile Pacú (Piaractus mesopotamicus) by supplementation with Pyropia columbina and β-carotene - Rossi, L.T.; Romero Scharpen, Analía; Zimmermann, Jorge Alberto; Olivero, Carolina Raquel; Zbrun, María Virginia; Frizzo, Laureano Sebastian; Signorini Porchiett, Marcelo Lisandro; Bacchetta, Carla; Cian, Raúl Esteban; Cazenave, Jimena; Soto, Lorena Paola; Drago, Silvina (Springer, 2021)
The aim was to evaluate the effects of diet supplementation with red seaweed Pyropia columbina or β-carotene on the intestinal microbiota of juvenile Pacú (Piaractus mesopotamicus). Three hundred and fifteen fish (body weight 12.4 ± 2.8 g) were stocked in nine 300-L tanks with 35 fishes per tank and fed for 62 days with a basal feed (BG) or the same feed added with P. columbina (35 g kg−1) (AG) or supplemented with β-carotene (225 g kg−1) (β-CG). From fecal samples of three fishes slaughtered per group at 20th, 41th, and 62th days, plate counts of bacterial populations (enterobacteria, lactic acid bacteria—LAB, total aerobes, and psychrotrophs) and DGGE were made. Enterobacteria counts were lower in AG-group than the other groups throughout the experience (p = 0.016). LAB/enterobacteria ratio was greater in fishes supplemented with AG on 20th day, showing a greater amount of beneficial bacteria than non-beneficial ones. DGGE profiles resulting from the microbiota of β-CG at 62th day were clustered and separated from the rest of the profiles with a difference of 91%. Margalef richness (p = 0.049) and Shannon diversity index (p = 0.044) were lower in β-CG than in AG at 62th day. Taxonomic characterization showed the presence of three phylum: Bacteroidetes, Firmicutes, and Fusobacteria. This is the first study in which the microbiota of juvenile Pacú fed with biofunctional diets was evaluated. Future interventions that modify the bacterial ecosystem could improve the productive performance and ensure the safety of the pacu meat intended for consumption.